2006
DOI: 10.1093/brain/awl011
|View full text |Cite
|
Sign up to set email alerts
|

Disgust-specific impairment of facial expression recognition in Parkinson's disease

Abstract: There is contradictory evidence regarding whether the impairments of the recognition of emotional facial expressions in Parkinson's disease are specific to certain emotions such as disgust and fear. Generally, neurological case reports on emotion-specific impairments have been suspected of being confounded with the factor of task difficulty. Using a refined assessment method in which the difficulty factors were controlled by means of mixed facial expressions and item response theory, we attempted to clarify wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
138
6
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 189 publications
(170 citation statements)
references
References 94 publications
(164 reference statements)
17
138
6
9
Order By: Relevance
“…In line with other studies that reported impaired emotional recognition in PD patients (Lawrence, Goerendt, & Brooks, 2007;Suzuki et al, 2006;Sprengelmeyer et al, 2003), we found a significant decrease of recognition of emotional but not nonemotional gestures in the PD patients. With respect to the specific recognition deficits of emotional gestures, we hypothesized that a decrease in left BA 47 activation should correlate with decreased left putamen DAT, which indeed was the case; access to BA 47 seems to be modulated by dopaminergic activity in the left putamen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with other studies that reported impaired emotional recognition in PD patients (Lawrence, Goerendt, & Brooks, 2007;Suzuki et al, 2006;Sprengelmeyer et al, 2003), we found a significant decrease of recognition of emotional but not nonemotional gestures in the PD patients. With respect to the specific recognition deficits of emotional gestures, we hypothesized that a decrease in left BA 47 activation should correlate with decreased left putamen DAT, which indeed was the case; access to BA 47 seems to be modulated by dopaminergic activity in the left putamen.…”
Section: Discussionsupporting
confidence: 93%
“…The motor impairment often is accompanied by neuropsychological deficits (Dubois & Pillon, 1997), including abnormalities in emotional processing, such as impaired perception of vocal material [prosody (Pell, 1996;Blonder, Gur, & Gur, 1989); vocal emotions (Breitenstein, Van Lancker, Daum, & Waters, 2001)], as well as visual recognition of emotional (Suzuki, Hoshino, Shigemasu, & Kawamura, 2006;Kan, Kawamura, Hasegawa, Mochizuki, & Nakamura, 2002;Breitenstein, Daum, & Ackermann, 1998) and nonemotional faces (Dewick, Hanley, Davies, Playfer, & Turnbull, 1991). Selective deficits in recognition of facial expressions of disgust are observed in symptomatic PD patients as well as in patients with presymptomatic Huntington's disease, an illness associated with neuronal loss in the striatum (Suzuki et al, 2006;Hennenlotter et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, facial recognition impairments may be mitigated when patients are receiving dopaminereplacement therapy, as indicated by reduced error rate for medicated PD participants compared to medication-free PD participants when identifying disgust. 13 Somewhat consistent with the findings of Sprengelmeyer et al, 13 Suzuki et al 14 found an emotion recognition deficit for participants in the early stages of idiopathic PD, all of whom were receiving dopamine replacement therapy, that was specific to disgust. Evidence from early studies investigating emotion identification impairment in PD emphasized the need for clarification when nuances, such as medication status, were considered.…”
Section: Impaired Emotion Recognition In Pdsupporting
confidence: 71%
“…More specifically, they rate a target expression on a set of emotional visual analog scales (VAS). Few studies used rating tasks,30, 32, 33, 56, 70, 71, 72 but all except one71 highlighted an FER deficit among patients. However, when intensity ratings were dichotomized as correct (when the scale corresponding to the target emotion had the highest intensity rating) versus incorrect, the deficit was not always reported 33, 72.…”
Section: Discrepancies In Resultsmentioning
confidence: 99%